Association of Depression and Anxiety With the 10-Year Risk of Cardiovascular Mortality in a Primary Care Population of Latvia Using the SCORE System - Ivanovs, Rolands; Kivite, Anda; Ziedonis, Douglas; Mintale, Iveta; Vrublevska, Jelena; Rancans, Elmars (Frontiers in Psychiatry, 2018)
Background: Depression and anxiety have been recognized as independent risk factors for both the development and prognosis of cardiovascular (CV) diseases (CVD). The Systematic Coronary Risk Evaluation (SCORE) function measures the 10-year risk of a fatal CVD and is a crucial tool for guiding CV patient management. This study is the first in Latvia to investigate the association of depression and anxiety with the 10-year CV mortality risk in a primary care population. Methods: This cross-sectional study was conducted at 24 primary care facilities. During a one-week period in 2015, all consecutive adult patients were invited to complete a nine-item Patient Health Questionnaire (PHQ-9) and a seven-item Generalized Anxiety Disorder scale (GAD-7) followed by sociodemographic questionnaire and physical measurements. The diagnostic Mini International Neuropsychiatric Interview (M.I.N.I.) was administered by telephone in the period of two weeks after the first contact at the primary care facility. A hierarchical multivariate analysis was performed. Results: The study population consisted of 1569 subjects. Depressive symptoms (PHQ-9≥10) were associated with a 1.57 (95% confidence interval (CI): 1.06-2.33) times higher odds of a very high CV mortality risk (SCORE≥10%), but current anxiety disorder (M.I.N.I.) reduced the CV mortality risk with an odds ratio of 0.58 (95% CI: 0.38-0.90). Conclusions: Our findings suggest that individuals with SCORE≥10% should be screened and treated for depression to potentially delay the development and improve the prognosis of CVD. Anxiety could possibly have a protective influence on CV prognosis.